The Effect of Video-Based Education on Pregnant Women’s Knowledge Regarding Triple Elimination Screening - Tauba, Ahmad Mumtaz; Rua, Yusfina Modesta; Nahak, Maria Paula Marla (Genius Journal, 2026)
Introduction: Maternal to child transmission of infectious diseases such as HIV, syphilis, and hepatitis B remains a major global health concern. The “Triple Elimination” program integrates early detection and prevention strategies for these infections within maternal health services. However, limited maternal knowledge and awareness impede optimal screening participation, especially in developing regions. Educational interventions using audiovisual media such as videos have shown promise in improving maternal understanding and promoting health-seeking behavior. Objective: To determine the effect of video-based education on the knowledge of pregnant women regarding triple elimination screening at RSUD Mgr. Gabriel Manek, SVD., Atambua, Belu. Method: A quasi-experimental study with a one-group pretest-posttest design was conducted among 32 pregnant women attending antenatal care (ANC) during October–November 2025. Participants received an educational intervention using a health education video about triple elimination. Data on knowledge were collected using a validated questionnaire, and statistical analysis was performed using the Wilcoxon signed-rank test with a significance level of p < 0.05. Result: The median knowledge score before the intervention was 13 (minimum 5; maximum 15), while after the intervention it increased to 16 (minimum 13; maximum 16). Statistical analysis revealed a significant difference in pretest and posttest scores (p < 0.001), indicating that video-based education effectively improved maternal knowledge. Conclusion: Video-based education significantly enhances pregnant women’s knowledge regarding triple elimination screening. The use of audiovisual media in maternal health education should be integrated into antenatal services to strengthen awareness and early detection of HIV, syphilis, and hepatitis B.